Holocene evolution of the microbial deposits in the Clifton-Preston lake system, Western Australia - Lluesma Parellada, Alonso (Curtin University, 2015)
The goal of the project was to study the evolution of the microbial communities during the Holocene in the lakes at the Yalgorup National Park, with focus on the thrombolite reef located at Lake Clifton. The project provided useful insights, information and a better understanding of the genesis, internal textures/fabrics and external morphologies controls over the microbialites, beyond to analyze actual hydrochemistry of lakes in area and the environmental human influence over it.